2004
DOI: 10.1111/j.1651-2227.2004.tb02938.x
|View full text |Cite
|
Sign up to set email alerts
|

Impulse control, working memory and other executive functions in preterm children when starting school

Abstract: Aim: The aim of this study was to explore whether children born preterm have deficient executive functions (EF) in comparison with children born at full term, and, if so, whether this is dependent on inferior intelligence scores and can be correlated to specific neonatal risk factors and gender. Methods: In a population‐based study, the executive functions of 182 preterm children (birthweight less than 1500 g, VLBW) and 125 controls from the Stockholm Neonatal Project were assessed at 5± y with a neuropsycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
4
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 34 publications
10
82
4
5
Order By: Relevance
“…It was found that 6-year-old children born with LBW show nonverbal WM deficits, and also planning and cognitive flexibility deficits (26). In another study, WM deficits were found in 5½-year old children born with LBW, but these children had all been born preterm (27). The findings in our experiment suggest that the piglets in our experiment can indeed serve as a model for human SGA infants, and the cognitive pig hole board seems to be a task sensitive enough to detect these mild deficits.…”
Section: Articlesmentioning
confidence: 93%
“…It was found that 6-year-old children born with LBW show nonverbal WM deficits, and also planning and cognitive flexibility deficits (26). In another study, WM deficits were found in 5½-year old children born with LBW, but these children had all been born preterm (27). The findings in our experiment suggest that the piglets in our experiment can indeed serve as a model for human SGA infants, and the cognitive pig hole board seems to be a task sensitive enough to detect these mild deficits.…”
Section: Articlesmentioning
confidence: 93%
“…[48][49][50] There is some evidence that preterm boys perform more poorly than girls in general on tests of executive function. 51 However, it is not known whether this represents a group by sex interaction effect or merely a sex effect. Hippocampus, amygdala, and cingulate volumes were reduced in male preterm subjects compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Executive functions [5,9,10], attention [11,12,20,31,37], memory functions [10,11,20,33], visuomotor and visuospatial functions [11,12,20,33], as well as language functions [11,20,33,40] have been found to be affected by a preterm birth. Neuropsychological functions are usually studied using neuropsychological/psychological tests and test batteries administrated by a psychologist.…”
Section: Introductionmentioning
confidence: 99%